Production of decellularized porcine lung scaffolds for use in tissue engineering. Issue 12 (1st October 2015) - Balestrini, Jenna L.; Gard, Ashley L.; Liu, Angela; Leiby, Katherine L.; Schwan, Jonas; Kunkemoeller, Britta; Calle, Elizabeth A.; Sivarapatna, Amogh; Lin, Tylee; Dimitrievska, Sashka; Cambpell, Stuart G.; Niklason, Laura E.
Abstract : There is a growing body of work dedicated to producing acellular lung scaffolds for use in regenerative medicine by decellularizing donor lungs of various species. Abstract : There is a growing body of work dedicated to producing acellular lung scaffolds for use in regenerative medicine by decellularizing donor lungs of various species. These scaffolds typically undergo substantial matrix damage due to the harsh conditions required to remove cellular material ( e.g., high pH, strong detergents), lengthy processing times, or pre-existing tissue contamination from microbial colonization. In this work, a new decellularization technique is described that maintains the global tissue architecture, key matrix components, mechanical composition and cell-seeding potential of lung tissue while effectively removing resident cellular material. Acellular lung scaffolds were produced from native porcine lungs using a combination of Triton X-100 and sodium deoxycholate (SDC) at low concentrations in 24 hours. We assessed the effect of matrix decellularization by measuring residual DNA, biochemical composition, mechanical characteristics, tissue architecture, and recellularization capacity.